Static, Dynamic .And Notch Toughness ? Discussion (33ce9820-d9df-48aa-8737-a0482b352b93) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
J. E. JOHNSON, JR., New York.-It seems to me that it ought to be somebody's job to tie these notch tests with the reversed-stress tests, because the thing that causes failures in structures, in a great majority of cases, is where the material is stressed repeatedly up somewhere near the elastic limit, and the repetition of that stress seems to bring about what I suppose you may call a growth of crystals and that eventually develops into a break. It seems to me that it would be of the greatest value if there could be a coordination of the results of a shock test of some kind with the reversed-stress test, so that we could be sure that a material that had shock-test resistance would have reversed-stress resistance. H. F. MOORE,* Urbana, Ill.-The question raised by the speaker concerning the correlation of results from impact tests of notched bars with the results of repeated-stress tests is a very complicated one. Impact on a specimen sends energy into the specimen, and if the specimen absorbs this energy without fracturing there must be developed both stress and elongation. A notch in the specimen allows but little elongation to take place before rupture, and develops the ductility of the